Exploring the influence of intlawulo on father Involvement among Xhosa speaking black South African fathers raised and living in Cape Town - Samukimba, Jill Chidisha (Department of Sociology, 2020)
Studies on African fatherhood represent African fathers as problematic and in South Africa, they are identified as ‘‘emotionally disengaged, physically absent, abusive and do not pay for their children's upkeep'' (Morrell & Ritcher, 2006:81). Many studies link the high rates of absent fathers to poverty and irresponsibility. Such literature is devoid of cultural factors that might be contributing to the high rates of absent fathers in most African communities. Across Southern Africa, intlawulo, a customary practice that involves the paying of a fine by a man responsible for impregnating a woman out of wedlock and his family to the pregnant woman's family. Historically, intlawulo served as a critical means of regulating and mediating unmarried fathers' involvement in their children's lives. Therefore, this explorative qualitative research project explores African fathers' experiences of intlawulo and its subsequent links to father involvement. To gauge their experiences and interpretation of intlawulo and father involvement, I conducted face-to-face in-depth qualitative interviews with a purposive sample of 8 black Xhosa speaking South African fathers from Cape Town who have gone through the intlawulo negotiations for the past five years or less. This study aimed to explore how the customary practice of intlawulo or ‘paying damages' influences a father's involvement in his child's life in Khayelitsha, an urban township within Cape Town. It argued that the payment of intlawulo regulates a father's involvement in childrearing, his interaction with and access to his child. In contrast to how fathering has been described in previous literature, this thesis argues that becoming a father is a process and intlawulo is the entry point where it can be denied, stopped and negotiated.